Graeco-Arabic Astronomy for Twelfth-Century Latin Readers - Nothaft, Carl Philipp Emanuel (My University, 2022)
This volume makes available two little-known twelfth-century Latin sources on mathematical astronomy: the anonymous Ptolomeus et multi sapientum… (c.1145), which is attributable to the famous Jewish astrologer Abraham Ibn Ezra, and the surviving second part of Robert of Chester’s Liber canonum, which accompanied the Tables of London (c.1150). Both texts are introductory-level works originally written to educate a Latin Christian audience in the concepts and techniques involved in computing with astronomical tables. They are here presented in critical editions with facing English translations. The accompanying introductions and in-depth commentaries elucidate their significance in the context of twelfth-century Latin astronomy.
Keywords: medieval astronomy; manuscripts; twelfth century; Medieval Europe